Synthesis and characterization of a novel tungstosilicic acid immobilized on zeolites catalyst for the photodegradation of methyl orange - Leal Marchena, Candelaria (2016)
Materials based on tungstosilicic acid (TSA) immobilized on zeolites (NH4Y and NH4ZSM5) were prepared by wet impregnation of the zeolite matrix with TSA aqueous solutions. The concentration was varied in order to obtain TSA contents of 5%, 10%, 20%, and 30% w/w in the solid. Catalysts were further characterized by N2 adsorption–desorption isotherms, FT-IR, XRD, DRS-UV–vis and SEM techniques. The resulting materials were evaluated in the photodecomposition of azo dye methyl orange. The results revealed that the materials present suitable properties to be used as catalysts in the photocatalytic treatment of wastewater containing dyes, and the photodegradation follows a pseudo-first-order kinetics. Reaction parameters such as TSA content, catalysts mass, reuses and pH, were evaluated.